Contemporary deformation study along Cambay and Narmada paleo-rift system, western part of Indian plate - Rakesh K. Dumka (Quaternary Science Advances, 2024)
The western part of the Indian plate, which includes three major paleo-rifts, the Kachchh, Narmada and Cambay basins, is tectonically active and has seen moderate to large earthquakes. Regional stress due to the convergence of the Indo-European plates is the main cause of deformation accumulation in this section. However, a number of local strain accumulation factors within the plate also appear to be responsible. In the present study, we conducted GNSS-based deformation analysis along the Cambay Rift-Basin and Narmada Rift Basin (CRB and NRB) using GNSS datasets spanning over a decade (2009–2020). An average deformation of ∼1.2 ± 0.2 mm/year and a maximum strain of 2 × 10−08 strains/year are associated along these two ancient rift systems. The cross and along motion of GNSS sites relative to the NRB indicates dextral movement along the CRB. Furthermore, the motion of GNSS sites was analyzed to see the motion along these two rift systems and prepared a schematic model to understand the genesis of earthquakes in the study area. We found two locations of maximum stress accumulation in the study area. The stress distribution as well as the local geological structures are the main causes of stress accumulation and seismicity in the northern part of the CRB. The stress acting from the north and south form a compression zone along the NRB. GNSS derived strain analysis indicate accumulation of extensional strain towards the northern part of the CRB and therefore, generating dip-slip as well as the strike-slip earthquakes in the region. The study recognizes the role of lineaments, Paleo-rift margins as well as geological trends and fold systems in the present-day seismo-tectonics of Western India.